The vulnerabilities of the Brazilian health workforce during health emergencies : analysing personal feelings, access to resources and work dynamics during the COVID-19 pandemic - Lotta, Gabriela (2021)
Public health emergencies are a test of resilience for health systems, which depend on health workforces that are well managed and cared for. The COVID-19 pandemic exposed the weakness of many health systems in preparing their health workforces. The crisis also exacerbated the unequal conditions between different professions, an issue that is still understudied in the workforce literature. This paper analyzes the consequences of the COVID-19 pandemic for different health professionals, considering the ways in which Brazil's the health system does or does not protect them. We also analyse the role of pre-existing inequalities between different professions and social groups within the workforce in shaping their different experiences of the pandemic. We present data comparing the perceptions of different health professionals facing the pandemic in Brazil: physicians, nurses, and community health workers. Data were collected in an online survey in Brazil with 1630 health care workers between June 15th and July 1st. Findings suggest that none of the professions felt well prepared to work under emergencies. However, differences relating to professional background were exacerbated during the pandemic, creating unequal conditions for different health workers. These inequalities may pose new challenges for the post-pandemic scenario.